Entre histoire sociale des conflits et histoire des concepts : protestation et ordre public en Espagne dans le dernier tiers du xixe siècle - François Godicheau (Les Cahiers de Framespa)
The history of social conflicts in contemporary Spain has been richly documented in many books and through various approaches. Nevertheless, the overview we propose reveals a scattering trend in the investigations, certainly because of a tendency to naturalise the categories of the «social» and the «political»; as well because of the recurrent presence in nineteenth century political discourse of concepts referring to some realities: important political phrases like «public order» or popular disorder figures like «bandits» or «anarchists». As part of a research program financed by the French National Research Agency, entitled «The imperial renewal of the Iberian states: an early form of globalisation? (1808-1930)» (program called GLOBIBER), a collective investigation is conducted on issues of public order in this context of Spanish imperial renewal; it is an opportunity for a systematic enquiry about social and political conflictuality concepts and categories in modern and contemporary Spain. The historical object we are proposing grows from the association of social and conceptual approaches in a context of connected histories; it also contains a methodological section, based on the processing of a big database, in a complex way, combining network and lexicon analysis.